Evidence-based support to change the modalities of Egypt's food subsidy system for better effectiveness and improved nutrition and food security impacts - CGIAR Research Program on Policies, Institutions, and Markets (2020)
Since 2012, PIM has provided support to the longstanding partnership between IFPRI and the Government of Egypt to reform the country’s food subsidy system for better effectiveness and improved nutrition and food security impacts. The most recent round of reform is ongoing and aims at better targeting the system’s beneficiaries.